2014
DOI: 10.1039/c4nr00458b
|View full text |Cite
|
Sign up to set email alerts
|

Reducing ZnO nanoparticle cytotoxicity by surface modification

Abstract: Nanoparticulate zinc oxide (ZnO) is one of the most widely used engineered nanomaterials and its toxicology has gained considerable recent attention. A key aspect for controlling biological interactions at the nanoscale is understanding the relevant nanoparticle surface chemistry. In this study, we have determined the disposition of ZnO nanoparticles within human immune cells by measurement of total Zn, as well as the proportions of extra- and intracellular dissolved Zn as a function of dose and surface coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 49 publications
6
63
0
Order By: Relevance
“…With the presence of LNA, ZnO NPs and BSA-induced Zn ion accumulation was not significantly affected in HepG2 cells. Previous work showed that the presence of vitamin C enhanced the toxicity of ZnO NPs due to the enhanced accumulation of intracellular Zn ions [6], whereas surface modifications of ZnO NPs could reduce the cytotoxicity of NPs by the reduction of NP uptake and, subsequently, the accumulation of intracellular Zn ions [37]. Thus, the unaltered cytotoxicity of ZnO NPs and BSA to HepG2 cells with the presence of LNA could be explained in that LNA did not significantly promote the accumulation of Zn ions into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…With the presence of LNA, ZnO NPs and BSA-induced Zn ion accumulation was not significantly affected in HepG2 cells. Previous work showed that the presence of vitamin C enhanced the toxicity of ZnO NPs due to the enhanced accumulation of intracellular Zn ions [6], whereas surface modifications of ZnO NPs could reduce the cytotoxicity of NPs by the reduction of NP uptake and, subsequently, the accumulation of intracellular Zn ions [37]. Thus, the unaltered cytotoxicity of ZnO NPs and BSA to HepG2 cells with the presence of LNA could be explained in that LNA did not significantly promote the accumulation of Zn ions into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 shell coating of ZnO NPs was reported to decrease their toxicity by controlling the rate of Zn 2+ ion release when interacting with cells [34]. Alternatively, alteration of surface properties of ZnO NPs, which may in turn affect their uptake rather than changing dissolution characteristics of the material, was recommended by Luo et al [35]. Novel strategies specifically targeting the dissolution tendency of ZnO NPs may help to enhance safe use of these materials in the biomedical area.…”
Section: Zno Nps Cell Interaction and Cytotoxicitymentioning
confidence: 97%
“…There is a degree of commonality across studies, in which smaller NPs tend to exhibit greater cytotoxicity (on a per mass basis) and that the required concentrations for cytotoxicity tend to be very high, while ZnO NPs are as well tolerated as zinc ions (Xia et al 2008;Feltis et al 2012;Shen et al 2013Shen et al , 2014. The mechanism for cytotoxicity relates to the elevated production of intracellular ROS via zinc displacement of other transition metal ions that are redox active, and is a function of particle surface area and coating, cellular uptake and lysosomal dissolution (Fukui et al 2012;Sharma et al 2012;James et al 2013;Shen et al 2013;Luo et al 2014).…”
Section: Introductionmentioning
confidence: 97%